Study on Pulsation Law of Gas-Liquid Two-Phase Flow in Produced Water Dissolved Gas System - Jiang, Shuxuan; Lu, Peiyu (Scientific Journal of Technology, 2026)
This study focuses on the pulsation characteristics of gas-liquid two-phase flow in undulating pipe networks and adopts a one-dimensional model. The results show that the pulsation of gas-liquid two-phase flow causes an increase in pressure at the manifold inlets of each well accompanied by a certain degree of pulsation. The pulsation exhibits a significant wide-frequency distribution feature, where high-frequency pulsations are mainly caused by the operation of pumping units, and low-frequency pulsations originate from random slug flow of two-phase flow in undulating pipelines. Meanwhile, the increase in single-well water production promotes the rise of pressure at the manifold inlets of each well, and the degree of pressure pulsation shows a decreasing trend. The results of this study can provide a theoretical basis for the stable operation and pressure regulation of gas-liquid two-phase flow in undulating pipe networks.